Monitoring magnetik terhadap polusi kendaraan bermotor di Kota Padang Panjang (Magnetic monitoring of pollution due to vehicles in Padang Panjang City) - Delta Perdana (PILLAR OF PHYSICS, 2016)
Air pollution caused by vehicle has reached alarm point basically in a big city caused by human activity such as industria process, vehicle emission, household trash burning and more another activity. Air Pollution caused by vehicle  produced magnetic mineral that sourced from friction machine, corotion of vehicle machine and vehicle emission  that from incomplete combustion, where tha source of pollution in form of fly ash, so that cause air pollution. Padang Panjang include areas vehicle pass so that must doing research about magnetic monitoring to pollution by vehicle in Padang Panjang city. Purpose of this research for determinethe air pollution caused vehicle. In this research taking  30 topsoil as sample.air pollution level can determined by using rock magnetism method that is Magnetic Suseptibility method. Suseptibility magnetic Method used to know concentration or magnetic suseptibility value that be contained in a sample. Magnetic susceptibility value be measured with using  Bartington Susceptibility Meter MS2B type. Measurement made by mass suseptibility value. Suseptibility value can  be determined pollution levels (high, medium, and low). Based on measurement obtainable average magnetic suseptibility value all of sample taking point sample include ranges 1133,3 x 10-8 m3/kg until 1263,9 x 10-8 m3kg-1, including high polluted category. Highest magnetic suseptibility value there in Ngalau villages which indicates high pollution levels. Judging from the distance measurements from a roadside in Padang Panjang, the highest susceptibility values are at a distance of 0 m from the roadside then 1 m and 2 m from the roadside